PENGARUH IKLAN DAN PROMOSI PENJUALAN TERHADAP NIAT PERILAKU YANG DIMEDIASI OLEH CITRA MEREK PADA PENGGUNA SCARLETT WHITENING DI BANDA ACEH - nurhamidah daulay; Abdul Rahman Lubis (Departemen Manajemen, 2023)
This study aims to measure the effect of advertising and sales promotion on behavioral intention mediated by brand image among Scarlett Whitening users in Banda Aceh City. The sample used in this study was consumers using Scarlett Whitening in Banda Aceh City, totaling 200 people. Data collection equipment used in this study is a questionnaire. The sampling technique used is purpsive sampling, structural equation modeling (SEM) is used as an analytical method to determine the influence of the variables involved. Based on the results of the SEM analysis identified that advertising has a positive effect on behavioral intention, sales promotion has a positive effect on behavioral intention, advertising has a positive effect on brand image, sales promotion has a positive effect on brand image, brand image has a positive effect on behavioral intention, brand image mediates the influence of advertising on behavioral intention, and brand image mediate the effect of sales promotion on behavioral intention